Parenting Style and Resilience among Homosexual in Indonesia - Ruly Feby Kurniasari; Arthur Huwae (Journal La Sociale, 2024)
This study aims to determine the relationship of parenting styles and resilience in homosexuals (gay) in Indonesia. The research method used is quantitative with correlational design. A total of 454 homosexuals (gay) in Indonesia are used as participants using incidental sampling techniques. The measurement of this study used the Parental Authority Questionnaire (PAQ) scale with fathers’ authoritarian parenting style (α = .868), fathers’ authoritative parenting style (α = .766), fathers’ permissive parenting style (α = .768), mothers’ authoritarian parenting style (α = .868), mothers’ authoritative parenting style (α = .843), mothers’ permissive parenting style (α = .746), and the Resilience Quotient Scale (RQ) (α = .873). Data analysis was conducted using Karl Pearson's product-moment correlation test. The results of this study indicated that there is no relationship between fathers’ authoritarian parenting style and resilience (r = .065 and sig. = .084). Likewise, for the fathers’ authoritative parenting style, it showed no relationship with resilience (r = .003 and the sig. = .472). Similarly, there was no significant relationship found between fathers’ permissive parenting style and resilience (r = -.034 and sig. = .235). The results also revealed that there is no relationship between mothers’ authoritarian parenting style and resilience (r = .008) and sig. = .435). Likewise, no significant relationship was found between mothers’ authoritative parenting style and resilience (r = .005 and sig. = .457). Furthermore, the study found no relationship between mothers’ permissive parenting style and resilience (r = .015 and sig. = .379).